DETERMINATION OF CERTAIN INTEGRAL PARAMETERS ASSOCIATED WITH ARTERIAL HYPERTENSION IN OBESE CHILDREN - Lezhenko, Hennadii; Pashkova, Olena; Samoylyk, Kateryna (Eastern Ukrainian Medical Journal, 2025)
The aim of the study: Stratification of integral indicators determining the risk of developing arterial hypertension in obese children. Materials and methods. The observation group consisted of 139 obese children aged 11–17 years, who were divided into two subgroups depending on the level of blood pressure (BP). The first subgroup included 50 (36 %) adolescents with obesity and hypertension. The second subgroup consisted of 89 (64 %) children with normal blood pressure. The comparison group consisted of 36 conditionally healthy children, representative of age and gender. To identify the least possible number of latent common factors that have the greatest impact on the development of hypertension in obese children and determine their factor loadings, factor analysis by the principal component method was used, followed by orthogonal VARIMAX rotation of the factor axes. Significant factors in the model were examined using the scree-test and the Kaiser criterion, followed by the identification of indicators with a high factor loading on the complex (over 0.6). Results. Using factor analysis, 4 significant factors were identified, the dispersion of which determined 79.23 % of the contribution of all factors: 1) the factor of carbohydrate metabolism disorders, which included fasting glucose, the insulin sensitivity index QUICKI, and the insulin resistance index HOMA; 2) biological factor (gender and age of the child); 3) autonomic regulation factor (circadian heart rate index); 4) metabolic factor, which includes body mass index, waist-to-height ratio and serum cortisol level. It has been proved that hyperinsulinemia and insulin resistance are the leading factors contributing to the development and progression of hypertension in obese children. Conclusions. The obtained factor model will allow optimizing approaches to preventing the development and progression of hypertension in obese children by identifying a risk group for the development of arterial hypertension, taking into account the identified factors.